"A Mixed Blessing": Social Support as a Coping Resource for Parents Who Lost a Child in Terrorist Attacks in Israel. (December 2019) - Saka, Yael
This article deals with the issue of perceived social support among 40 bereaved parents who have lost a child in a terrorist attack in Israel. The aim is to gain a better understanding of the nature and quality of the formal and informal support that the parents received. The parents were interviewed using semistructured in-depth interviews. The content analysis revealed that alongside the positive aspects, the parents also emphasized the negative side of the encounter with the social environment. The positive aspects included feeling of appreciation for the assistance in the coping process. The negative aspects included a sense of abandonment and distress. The dialectic nature of the domain, together with a recognition of its importance, points to the need to reconcile between the desire on the part of the social environment to assist the bereaved parent on one hand and ways to implement it on the other hand.